Determinan Keberlanjutan Keuangan Pemerintah Daerah Kabupaten dan Kota di Provinsi Lampung - Siska Amelia; Rindu Rika Gamayuni (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study discusses the factors that influence the financial sustainability of districts and cities in Lampung Province during the 2017-2023 period. The main phenomenon behind this is the fluctuating and negative trend of financial sustainability since the COVID-19 pandemic, as well as an increase in the number of elderly and children who have the potential to hamper economic growth and regional fiscal capacity. This study aims to analyze the influence of financial independence variables, budget solvency, GRDP per capita, and population dependency ratio on regional financial sustainability. The method used is descriptive quantitative analysis with secondary data from regional financial reports, GRDP, and demographic data from BPS, with a sample of all districts / cities in Lampung totaling 15 regions and the period 2017-2023. The results show that financial independence and budget solvency have a positive and significant effect on financial sustainability, while GRDP per capita and population dependency ratio have no significant effect. The findings suggest that local governments should increase own-source revenues and maintain budget balance to strengthen local financial sustainability in the future.